1979
DOI: 10.1007/bf01961379
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of photoreceptor membrane vesicles

Abstract: The n-alkyl bromides with 6 to 10 carbons induce formation of vesicles of 5 to 100 micrometer diameter from the small vesicles (0.1 micrometer average diameter) produced by disruption of the discs from frog rod photoreceptors. The n-alkanes, n-alkyl iodides and n-alkyl chlorides are relatively ineffective. The formation of large vesicles is independent of calcium concentration and is distinguished from fusion processes previously reported by the large number of vesicles involved. The results reported here toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Ahkong et al reported that hen erythrocytes fuse on incubation with hydrocarbons 20. Mason et al subsequently reported that large native membrane vesicles (0.1–0.2 μm) from frog retinas fuse to form giant vesicles (5–100 μm) upon incubation with hydrocarbon halides, more specifically n ‐hexyl bromide 21. Key findings from this study were that 1) giant vesicles contained aqueous buffer and not oil, 2) giant vesicles did not contain large vesicles or membrane fragments and 3) giant vesicle formation arises from consecutive fusions of large vesicles rather than rupture and resealing 21.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahkong et al reported that hen erythrocytes fuse on incubation with hydrocarbons 20. Mason et al subsequently reported that large native membrane vesicles (0.1–0.2 μm) from frog retinas fuse to form giant vesicles (5–100 μm) upon incubation with hydrocarbon halides, more specifically n ‐hexyl bromide 21. Key findings from this study were that 1) giant vesicles contained aqueous buffer and not oil, 2) giant vesicles did not contain large vesicles or membrane fragments and 3) giant vesicle formation arises from consecutive fusions of large vesicles rather than rupture and resealing 21.…”
Section: Resultsmentioning
confidence: 99%
“…Mason et al subsequently reported that large native membrane vesicles (0.1–0.2 μm) from frog retinas fuse to form giant vesicles (5–100 μm) upon incubation with hydrocarbon halides, more specifically n ‐hexyl bromide 21. Key findings from this study were that 1) giant vesicles contained aqueous buffer and not oil, 2) giant vesicles did not contain large vesicles or membrane fragments and 3) giant vesicle formation arises from consecutive fusions of large vesicles rather than rupture and resealing 21. Morigaki and Walde further showed that large vesicles composed of fatty acids, such as oleic acid, fuse to form giant vesicles on coverplate glass with squalane (oil) adsorbed onto the surface 22.…”
Section: Resultsmentioning
confidence: 99%
“…Among them n -hexyl bromide (Figure 6; n = 6), octyl bromide ( n = 8), and decyl bromide ( n = 10) are known to have the desired fusogenic property [94]. These molecules can induce fusion at a very low molecule-to-lipid ratio (M : L) of 0.05 (for n = 6) [95], and they can induce cellular or subcellular membrane fusion [96] along with the fusion of biomimetics like PC-phosphatidic acid (PC : PA) mixed vesicles. Multilamellar vesicles (MLVs) of PC or PC : PA mixed lipids are used for experiments.…”
Section: Fusion Induced By Different Fusogenic Agentsmentioning
confidence: 99%
“…The osmotic integrity of rod outer segments in 0.6M sucrose seemed to be stabilized by 1 mM CaCl, [ 1071. Vesicles of 5 100 pn diameter were prepared by fusion of frog disks with n-alkyl bromides [74]. Whether the fused membrane retained the same sidedness as intact disk membrane was not investigated.…”
Section: /"mentioning
confidence: 99%